Merasakan Tasawuf - Anieg, Mukhamad (Kopertais Wilayah X Jawa Tengah, 2016)
AbstractAwareness has inspired humans to feel Suï¬ sm. Various kinds of questions lie about mutasawiï¬ n, including Who am I? Where am I? For what I created? How do I ï¬ ll out alive? What am I looking for? What kind of life I want to pick up after death? If I could go back to my native place safely? And other fundamental questions in human beings. Religion deifying vehicle, Iman deifying fuel, and the man who drove, the religion with the contents of the sentences noble in heart, it was the straight path. Th e way of approaching Him is to continue to multiply zikrullah. Zikir is the parent of worship, then where is the zikir when penetrating into the heart of a clean then it will feel the souls kesuï¬ an true. Hearts (qolbu) can also be likened to building a house. He was surrounded by walls and secured with a gate or gate locked. Only family members and guests who comes who may enter it. While the heart of the deeper (lubb) is a locked room that holds valuable heirlooms belonging to the family. Only a few family members who have the key. So when the door was open means opened the doors of Suï¬ sm in human beings and to feel the pleasure that can perform worship and all the good deeds that will save people in the world and the hereafter.Keyword: Suï¬ sm, qolbu, zikir